2012
DOI: 10.1186/1471-2407-12-107
|View full text |Cite
|
Sign up to set email alerts
|

The outcome and predictive factors of sunitinib therapy in advanced gastrointestinal stromal tumors (GIST) after imatinib failure - one institution study

Abstract: Background Gastrointestinal stromal tumors (GIST) mutational status is recognized factor related to the results of tyrosine kinase inhibitors therapy such as imatinib (IM) or sunitinib (SU). Arterial hypertension (AH) is common adverse event related to SU, reported as predictive factor in renal cell carcinoma. The aim of the study was to analyze the outcomes and factors predicting results of SU therapy in inoperable/metastatic CD117(+) GIST patients after IM failure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
4
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 44 publications
6
36
4
3
Order By: Relevance
“…Whether prolonged treatment with a TKI, or previous treatments with cytokines (i.e., IFN/IL-2) or another TKI might influence the incidence or the course of thyroid dysfunction remains to be clarified. Among TKI approved for clinical use, sunitinib, a TKI mainly targeting angiogenic kinase-receptors, exposes patients to a higher risk of developing TKI hypothyroidism (14-71% of patients in prospective studies) (146)(147)(148)(149)(150)(151)(152)(153). Thyroid dysfunction has also been described with other antiangiogenic TKI, such as sorafenib, motesanib, pazopanib, cediranib, and linifarib, but at lower rates (Table 2).…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether prolonged treatment with a TKI, or previous treatments with cytokines (i.e., IFN/IL-2) or another TKI might influence the incidence or the course of thyroid dysfunction remains to be clarified. Among TKI approved for clinical use, sunitinib, a TKI mainly targeting angiogenic kinase-receptors, exposes patients to a higher risk of developing TKI hypothyroidism (14-71% of patients in prospective studies) (146)(147)(148)(149)(150)(151)(152)(153). Thyroid dysfunction has also been described with other antiangiogenic TKI, such as sorafenib, motesanib, pazopanib, cediranib, and linifarib, but at lower rates (Table 2).…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…In renal cell carcinoma patients receiving sorafenib/sunitinib, better clinical outcomes were seen when hypothyroidism developed (158,159,168,230). Interestingly, higher risk of hypothyroidism during sunitinib therapy has been significantly associated with VEGF-A/VEGFR-2 gene single-nucleotide polymorphisms (152), suggesting that TKIinduced thyroid dysfunction may depend on a specific genetic predisposition. However, in this study better survival did not correlate with TKI-induced hypothyroidism.…”
Section: Why Is It Important To Assess Thyroid Function In Cancer Patmentioning
confidence: 99%
“…Patients with exon 9 mutations require an escalated dose of imatinib [25], whereas certain patients, especially those with exon 11 mutations, show no benefit from imatinib dose escalation [26]. More recent studies [27,28] showed improved efficacy in sunitinib-treated patients with primary mutations in KIT exon 9 compared with exon 11. A limitation of the current study is that correlation between mutational status and sunitinib efficacy and safety were not examined.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothyroidism has been reported in sorafenib-treated patients with renal cancer and in sunitinib-treated patients with gastrointestinal stromal cancer [21,22]. Additionally, thyroid hormone replacement therapy improved fatigue in axitinib-treated patients with cancer [23].…”
Section: Fatiguementioning
confidence: 99%